ON THE ISSUE OF TEACHING FOREIGN LANGUAGES IN SECONDARY SCHOOL - Pulatova Shakhzoda Haydarovna; Tolibova Nodira Nosirovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses modern technologies for teaching foreign languages in secondary school, the use of which allows you to implement a student-centered approach to teaching a foreign language and allows you to solve a number of didactic problems.